THE ETHICS OF ARTIFICIAL INTELLIGENCE FROM A HADITH PERSPECTIVE: AFFIRMING MORAL RESPONSIBILITY AS THE FOUNDATION OF RELIGIOUS MODERATION IN THE DIGITAL ERA - Abdul Karim; Muhamad Yusup; Nasrullah; Lalu Ahmad Zaenuri (Tahiro : Journal of Peace and Religious Mederation, 2026)
The development of artificial intelligence (AI) has brought fundamental change to human life while simultaneously presenting complex ethical challenges: algorithmic bias, dehumanization, data misuse, and a crisis of moral accountability. Within the context of a plural and multicultural society, these challenges are not merely technical in dimension but also touch upon the realm of religious values, moderation, and social harmony as seen in various cases of generative AI-produced content (images, text, and synthetic audio) that have sparked religious controversy in Indonesia's digital space, ranging from representations of religious figures and symbols deemed inappropriate to fake sermons or fatwas generated by AI and circulated on social media. This research aims to analyze AI ethics through the lens of hadith by affirming moral responsibility as the foundation of religious moderation in the digital era. Using a qualitative approach with library research methods and hadith hermeneutic analysis, the study examines primary sources from the Kutub al-Sittah along with their commentaries (syarah), as well as contemporary literature on AI ethics and Islamic moderation. The findings show that the principles of AI ethics justice, transparency, accountability, beneficence, and non-maleficence share strong points of convergence with the values of the Prophet's hadith. The hadith on leadership accountability (HR. Bukhari-Muslim), the principle of lā ḍarar wa lā ḍirār (HR. Ibn Mājah), and the hadith on itqan (HR. al-Baihaqi) not only provide an ethical foundation for AI development, but also affirm the principle of wasaṭiyyah (the middle path) as the basis for moderation in technology governance. The resulting Islamic AI Ethics framework offers moral guidance for developers, users, and regulators so that AI may contribute to universal benefit, avoid digital radicalization, and reinforce the role of Islam as rahmatan lil-'ālamīn.